Implementasi Pengembangan Moral Anak Usia 5-6 Tahun - Dhea Ananda Septiana; Ulwan Syafrudin (FKIP UNILA, 2022)
Early Childhood is the most basic age of human moral formation, so that basic behavior and abilities are formed according to the stage of development. This placement aims to describe the implementation of moral development for children aged 5-6 in TK Islam Al Azhar Bandar Lampung with a research focus(1) of development programs; (2) the performance of learning in moral development; (3) a learning evaluation in moral development. The research method used was a qualitative approach. Data collection techniques through interviews, observations, documentation and field notes. Data source: pincipal, teacher and child. Data analysis techniques using Miles and Hubbernan models, including: data collection, data reduction, deduction data presentation and the deduction process. Research: development programs, which are planned for both recruitment and incidental programs that can support child moral development. Implement of learning, teachers develop a child’s morals by planning and carrying out learning using appropriate methods and models. Learning evaluations, teachers evaluate learning in the proper ways and evaluation tools. Penelitian ini bertujuan untuk mendeskripsikan implementasi pengembangan moral anak usia 5-6 tahun di TK Islam Al Azhar 49 Bandar Lampung dengan fokus penelitian (1) Program Pengembangan; (2) Pelaksanaan Pembelajaran dalam Pengembangan Moral; (3) Evaluasi Pembelajaran dalam Pengembangan Moral. Metode penelitian yang digunakan yaitu pendekatan kualitatif. Teknik pengumpulan data melalui wawancara, observasi, dokumentasi dan catatan lapangan. Sumber data: Kepala Sekolah, Guru dan Anak. Teknik analisa data menggunakan model Miles dan Hubberman, meliputi: pengumpulan data, reduksi data, penyajian data dan proses penarikan kesimpulan. Hasil penelitian: Program pengembangan, terdapat berbagai program-program yang direncanakan baik bersifat rutinan maupun bersifat insidental yang dapat mendukung pengembangan moral anak. Pelaksanaan pembelajaran, guru mengembangkan moral anak dengan merencanakan dan melaksanakan pembelajaran menggunakan metode dan model yang sesuai. Evaluasi pembelajaran, guru mengevaluasi pembelajaran dengan cara dan alat evaluasi yang tepat.Kata Kunci: Anak usia dini, guru, moral. DOI: http://dx.doi.org/10.23960/jpa.v8n1.24077